Exosomal circ_DLGAP4 promotes diabetic kidney disease progression by sponging miR-143 and targeting ERBB3/NF-κB/MMP-2 axis - Bai, Shoujun; Xiong, Xiaoyan; Tang, Bo; Ji, Tingting; Li, Xiaoying; Qu, Xiaolei; Li, Weiliang (Cell death & disease, 2020)
Diabetic kidney disease (DKD) is closely associated with the high risk of cardiovascular disease and mortality. Exosomal circRNAs can exert significant roles in the pathology of various diseases. Nevertheless, the role of exosomal circRNAs in DKD progression remains barely known. Circular RNA DLGAP4 has been reported to be in involved in acute ischemic stroke. In our study, we found exosomal circ_DLGAP4 was increased in the exosomes isolated from HG-treated mesangial cells (MCs), DKD patients, and DKD rat models compared with the corresponding normal subjects. Then, we observed that exo-circ_DLGAP4 significantly promoted proliferation and fibrosis of MCs cells. Moreover, to study the underlying mechanism of circ_DLGAP4 in regulating DKD, bioinformatics method was consulted and miR-143 was predicted as its target. The direct correlation between miR-143 and circ_DLGAP4 was validated in MCs. MCs proliferation and fibrosis were increased by circ_DLGAP4, which could be decreased by mimic-miR-143. Next, elevated expression of Erb-b2 receptor tyrosine kinase 3 (ERBB3) is involved in various diseases. However, the function of ERBB3 in DKD development remains poorly known. Next, ERBB3 was predicted as the downstream target for miR-143. It was displayed that circ_DLGAP4 promoted proliferation and fibrosis of MCs by sponging miR-143 and regulating ERBB3/NF-κB/MMP-2 axis. Meanwhile, the loss of exo-circ_DLGAP4 induced miR-143 and repressed ERBB3/NF-κB/MMP-2 expression in MCs. Subsequently, in vivo assays were performed and it was proved that overexpression of circ_DLGAP4 markedly promoted DKD progression in vivo via modulating miR-143/ERBB3/NF-κB/MMP-2. In conclusion, we indicated that exosomal circ_DLGAP4 could prove a novel insight for DKD development.